Customer relationship management and hotel performance: the mediating influence of marketing capabilities—evidence from the Malaysian hotel industry - Mohammed, Abdul Alem; Rashid, Basri; Tahir, Shaharuddin (Springer International Publishing AG, 2017)
The aim of this study is to assess the influence of customer relationship management (CRM) on marketing capabilities (planning and implementation) and organizational performance, through an analysis of the hotel industry in Malaysia.The study uses partial least squares to examine the mediating influence of marketing capabilities on the association between CRM and hotel performance.A survey of hotel managers was conducted, and a total of 152 usable questionnaires were obtained. The results enrich the literature by showing a positive relationship between CRM and hotel performance; they also indicate that marketing planning and implementation play a mediating role in the relationship between CRM and hotel performance. From the practical perspective, by understanding the relationship among the constructs in the research model, hotel managers could maximize use of their internal resources to improve organizational performance.